Isolation and complete genome analysis of neurotropic dengue virus serotype 3 from the cerebrospinal fluid of an encephalitis patient - Dhenni, Rama (PLoS Negl Trop Dis, 2018)
Although neurological manifestations associated with dengue viruses (DENV) infection have been reported, there is very limited information on the genetic characteristics of neurotropic DENV. Here we describe the isolation and complete genome analysis of DENV serotype 3 (DENV-3) from cerebrospinal fluid of an encephalitis paediatric patient in Jakarta, Indonesia. Next-generation sequencing was employed to deduce the complete genome of the neurotropic DENV-3 isolate. Based on complete genome analysis, two unique and nine uncommon amino acid changes in the protein coding region were observed in the virus. A phylogenetic tree and molecular clock analysis revealed that the neurotropic virus was a member of Sumatran-Javan clade of DENV-3 genotype I and shared a common ancestor with other isolates from Jakarta around 1998. This is the first report of neurotropic DENV-3 complete genome analysis, providing detailed information on the genetic characteristics of this virus.